Demo: A Security Infrastructure for Vehicular Information Using SDN, Intrusion Detection, and a Defense Center in the Cloud - Philipp Meyer and Timo Häckel and Falk Langer and Lukas Stahlbock and Jochen Decker and Sebastian A. Eckhardt and Franz Korf and Thomas C. Schmidt and Fabian Schuppel (2020 IEEE Vehicular Networking Conference (VNC), 2021)
Vehicular on-board communication is the basis for advanced driver assistance, autonomous driving, over-the-air updates, and many more. If unprotected, this infrastructure is vulnerable to manipulation and various attacks. As any networked system, future connected cars require robust protection, monitoring, and incidence management against cyber-attacks during their lifetime. We demonstrate an infrastructure that secures the in-vehicle communication system and enables the security management of an entire vehicle fleet. Our prototype-a real-world production car-uses an Ethernet backbone network. It implements protective measures using software-defined networking, anomaly detection technologies, and is connected to a cyber defense center in the cloud. We demonstrate how this combination can reliably detect and mitigate common attacks on the vehicle-including its legacy components.
Keywords: Automotive; Security; SDN; Networking; Network Anomaly Detection; IDS; Cloud Defense Center